2021
DOI: 10.1016/j.psj.2021.101193
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of day of hatch exposure to various Enterobacteriaceae on inducing gastrointestinal inflammation in chicks through two weeks of age

Abstract: Inappropriate microbial colonization can induce gastrointestinal ( GI ) inflammation may predispose poultry to opportunistic infections and reduce growth performance. Four independent experiments were completed to test ability of select Enterobacteriaceae isolates to induce GI inflammation. Experiments 1 and 2 included a non-inoculated control ( NC ), and a low ( L ), medium ( M ), or high ( H ) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…Incidences of yolk sac infection with different Salmonella serovars has been reported and led to yolk sac retention in commercial broilers ( 26 ). Recently, it has been shown that oral inculcation of E. coli (9.5 ×10 2 CFU/bird) was able to cause yolk sac infection with a mean value of 144 CFU/g of on day 2 p.i and persisted up to day 14 (mean value 10 4 CFU/g) ( 27 ). Oral inoculation of Salmonella Heidelberg (SHb) and SEn (phage type 4) in day-old SPF chicks resulted in lesions due to yolk sac infection on days 7 (SHb and SEn) and 14 p.i (SHb) ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Incidences of yolk sac infection with different Salmonella serovars has been reported and led to yolk sac retention in commercial broilers ( 26 ). Recently, it has been shown that oral inculcation of E. coli (9.5 ×10 2 CFU/bird) was able to cause yolk sac infection with a mean value of 144 CFU/g of on day 2 p.i and persisted up to day 14 (mean value 10 4 CFU/g) ( 27 ). Oral inoculation of Salmonella Heidelberg (SHb) and SEn (phage type 4) in day-old SPF chicks resulted in lesions due to yolk sac infection on days 7 (SHb and SEn) and 14 p.i (SHb) ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…4 C) and α1GP (orosomucoid, P < 0.05, Fig. 4 B) known as an early inflammatory marker in the gastrointestinal tract (GIT; Chasser et al., 2021 ). However, we did not notice any changes in earlier secreted inflammatory cytokines ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…f_Enterobacteriaceae (phylum Proteobacteria) enrichment is frequently coincidence with considerable gut pathology. Patients with inflammatory bowel disease exhibited higher abundance of Enterobacteriaceae, and the outgrowth of Enterobacteriaceae could reversely result in gastrointestinal cell apoptosis and inflammation [42][43][44] . The abundance of g_Escherichia-Shigella was positively correlated with the blood levels of pro-inflammatory cytokines, and could promote the secretion of endotoxins.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with inflammatory bowel disease exhibited higher abundance of Enterobacteriaceae, and the outgrowth of Enterobacteriaceae could reversely result in gastrointestinal cell apoptosis and inflammation. [42][43][44] The abundance of g_Escherichia-Shigella was positively correlated with the blood levels of pro-inflammatory cytokines, and could promote the secretion of endotoxins. In CGA plus EGCG supplementation group, g_Candidatus_Soleaferrea genus was identified as one of the key taxons possessing anti-inflammatory capacity and maintaining the gut homeostasis.…”
Section: Papermentioning
confidence: 99%